The Role Of Cooperative Education In Economic Development Of Co-operators In Calabar Metropolis - Beshel, Cecilia A.; Anthony, Godwin Bullem (Advances in Social Sciences Research Journal, 2019)
Cooperative is seen as the joining efforts by a group of people with liked-minds to help each other out of a helpless situation with the aim of improving their conditions of living and for socio-economic improvement. One of the principles governing the operators of cooperatives has to do with cooperative education, to help in the achievement and sustenance of such cooperatives. This study was therefore carried out to investigate the role of cooperative education in the economic development of members in Calabar Metropolis. Four null hypotheses were formulated to guide the study. Literature was reviewed based on the variables used for the study. The population of the study was 329 while a sample of 150 was drawn and used for the study. The questionnaire was the main instrument used for the study. Analysis was done using the one-way analysis of variance. The result of the analysis reveals that cooperative education influence co-operators in terms of the living standard of the co-operators, their businesses, employment opportunities and awareness on loan schemes. It was recommended that more societies should intensify their cooperative education activities.